KULIAH KERJA MAHASISWA (KKM) di MASA PANDEMI COVID-19 SEBAGAI SALAH SATU BENTUK PENGABDIAN KEPADA MASYARAKAT - Rehulina Tarigan (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The pandemic not only presents anxiety about health threats, but also the welfare of many employees due to layoffs. Some of small, medium and even large scale businesses were forced to go out of business. Universita Banten Jaya immediately responded positively to the impact that emerged in the community due to the Covid-19 pandemic by holding a Student Work Lecture with the theme "Increasing Community Productivity During the Covid 19 Period". With the Student Creativity Program scheme, students are expected to be able to actualize their ability to contribute to increasing productivity and even people's income by providing education on how to do activities while adhering to health protocols, sharing knowledge on how to make products that are needed to protect and increase endurance such as making masks from cloth, hand sanitizer from aloe vera and ginger extract balm. It is hoped that by sharing this knowledge, people can remain productive and even open new businesses in terms of manufacturing these products to improve their economy. The method used is in the form of an explanation of how to manufacture it along with the tools and materials needed for the product mentioned above. The process of making is uploaded to social media in the form of a video so that it can be accessed by the wider community. It is hoped that more and more people will remain enthusiastic, productive and even pursue the manufacturing business of the above products to improve their economy and open up new jobs.